2005
DOI: 10.1002/eji.200425436
|View full text |Cite
|
Sign up to set email alerts
|

The fate of heterologous CD4+ T cells during Leishmania donovani infection

Abstract: Little is currently understood about the consequences of chronic parasitic infection for the fate of memory CD4 + T cells that recognize heterologous antigens, e.g. resulting from prior infections or vaccination. Here, we address how Leishmania donovani infection affected the fate of non-cross-reactive (OVA)-specific memory CD4 + T cells. DO11 cells were adoptively transferred into naive recipient mice, which were then immunized to generate memory DO11 cells. After 6 weeks, mice were infected with L. donovani … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Previous mouse studies reported bystander activity in the presence of a chronic parasitic infection (L. donovani), associated with a strong inflammatory response [6]. In our case, non-specific stimulation of the activated OT-II cells by a pro-inflammatory environment was unlikely since no adjuvant was used at boosting, and could be excluded by the fact that injection of control protein had no effect.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Previous mouse studies reported bystander activity in the presence of a chronic parasitic infection (L. donovani), associated with a strong inflammatory response [6]. In our case, non-specific stimulation of the activated OT-II cells by a pro-inflammatory environment was unlikely since no adjuvant was used at boosting, and could be excluded by the fact that injection of control protein had no effect.…”
Section: Discussionmentioning
confidence: 52%
“…Such responses could contribute to the antigen-independent maintenance of T cells at different stages, including memory T cells. Our next goal is to test the effects of bystander stimulation on survival and functionality of transferred memory cells generated in vivo [6] rather than on cells stimulated in vitro, mimicking more closely our observations in human subjects [16]. Whatever the stage of the responding T cells, a balance between maintenance of memory and a potentially pathological effect of cytokine-activated cells must be struck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 A close parallel to our observations in human subjects was described recently in a mouse model where infection with Leishmania donovani led to expansion of adoptively transferred transgenic ovalbumin (OVA)-specific memory CD4 ϩ T cells. 32 In this case, OVA antigen was required, possibly to maintain the transferred cells, whereas in our case it is unlikely, but not impossible, that PPD or C albicans antigens or cross-reactive antigens persist in vivo. While definitive data on generation and survival of T mem cells can be obtained from transgenic and knockout mice, it is difficult to mimic the situation in human subjects who have a normal T mem -cell repertoire under continuous exposure to environmental antigens.…”
Section: Discussionmentioning
confidence: 56%
“…This might in part be owing to sequestration of CD45RO + CD4 T cells in lesional tissue. In mice, both heterologous T cells and those with specificity for the parasite accumulate in the VL spleen [57]. The specificity of splenic T cells that accumulate in the human VL spleen has not been addressed to date.…”
Section: Il-10 and Immunosuppression In Vlmentioning
confidence: 99%